Fundamentals of Entrepreneurship ENT300 : Mad Over Donuts/ Tarien Kasi… [et al.] - Kasi, Tarien; Elli, Joanna Julan; Abang Marzuki, Abang Muhammad; Hului, Anna; Awang Puting, Dayang Nurul Ain (2013)
The name of our company is "MAD OVER DONUTS". The business is in the form of partnership, which consists of five members. Each partner contributes certain amount of capital as agreed in our agreement. Our business activity focuses on providing the product and services based on our product; donut. Our company is located at Desa llmu, Kota Samarahan. All partners are entitled to participate in the business management and have all agreed that Tarien Anak Kasi as our General Manager, Joanna Julan Elli as our Marketing Manager, Abang Mohammad Bin Abang Marzuki as our Administration Manager, Anna Hului as our Operational Manager and Dayang Nurul Ain Binti Awang Puting as our Financial Manager.The team is lead by the General Manager and assisted by other managers. The General Manager is responsible in planning, organizing, leading and controlling the business.